The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0103-05822007000300007
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de prevalência de defeitos congênitos no Vale do Paraíba Paulista

Abstract: OBJETIVO: Estimar a prevalência de anomalias congênitas no Vale do Paraíba Paulista em 2002 e 2003. MÉTODOS: Estudo transversal com base em dados constantes na Declaração de Nascido Vivo (DNV), cujas informações estavam no portal da Secretaria da Saúde do Estado de São Paulo. As malformações foram descritas de acordo com o capítulo XVII do Código Internacional de Doenças (CID) 10, referente a variáveis maternas e do recém-nascido. A variável desfecho (dependente) foi a presença de anomalia congênita; as demais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
3
28

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 13 publications
1
13
3
28
Order By: Relevance
“…These results are similar to those found in the United States and in Europe. 3,13,18 The prevalence of BDs in the city of São Paulo is comparable to that of the city of Rio de Janeiro, according to SINASC data. 13 The higher frequency of recorded BDs belongs to the groups that are clinically perceptible at birth, whether because they are visible or because they show conditions incompatible with life (anencephalic newborns: N=15).…”
Section: Discussionmentioning
confidence: 77%
“…These results are similar to those found in the United States and in Europe. 3,13,18 The prevalence of BDs in the city of São Paulo is comparable to that of the city of Rio de Janeiro, according to SINASC data. 13 The higher frequency of recorded BDs belongs to the groups that are clinically perceptible at birth, whether because they are visible or because they show conditions incompatible with life (anencephalic newborns: N=15).…”
Section: Discussionmentioning
confidence: 77%
“…15,16,17,19 A associação entre as malformações congênitas e óbito neonatal precoce tem sido demonstrada em vários estudos. 15,16,20,21 Neste estudo, a frequência de malformações congênitas entre os recém-nascidos foi muito alta (92,5%), mostrando a sua importância nos óbitos precoces.…”
Section: Discussionunclassified
“…DOI: dx.doi.org/10.7322/jhdg.88972 revealing, even though with fails, the frequency of this problem in the country, as well as its most common types. It is necessary to highlight that, according to values observed worldwide, the estimated frequency of congenital malformations at birth can vary between 2 and 5% 8 , although some authors have observed higher values. Official data for Brazil show a frequency of 0.8% in 2011, which demonstrates that the undercount of these registers in the country still exists and is still high 9 .…”
Section: Introductionmentioning
confidence: 98%